NPR1 gene transformation as assessed by germ cell in situ transformation pathway into Siraitia grosvenorii - Li, Jing-Jian; Liu, Xin; Zhao, Bo; Li, Wen-Lan (Bangladesh Journal of Botany, 2018)
NPR1 gene was transformed into Siraitia grosvenorii (Swingle) C. Jeffrey ex. A.M. Lu and Zhi Y. Zhang by germ cell in situ transformation. Ovary injection, cutting chapiter, and chapiter spreading treatments were applied in this study. The transgenic plants were selected using hygromycin screening and confirmed by PCR testing, genome integrated with NPR1 gene in transgenic plants was analyzed by Southern hybridization. Results showed that three treatments could produce transgenic plants. Some of the transgenic plants were selected for tobacco mosaic virus inoculation testing, which showed a higher level of resistance to tobacco mosaic virus than non-transgenic controls.